Pengaruh Citra Merek dan Kepercayaan Terdahap Loyalitas Nasabah Bank Syariah di Sidoarjo (The Influence of Brand Image and Trust on Sharia Bank Customer Loyalty in Sidoarjo) - Muhammad Amirul Mukminin; Fitri Nur Latifah (Perisai : Islamic Banking and Finance Journal, 2020)
One of the marketing strategies at Islamic banks is by building a company's brand image and customer trust to gain customer loyalty. The focus of this research is to show the relationship between brand image, trust and loyalty of Syariah bank customers in Sidoarjo. This study uses a random sampling technique with 100 customers of Islamic banks domiciled in Sidoarjo and at least have become customers of Islamic banks within one year. The analytical method used in this study is a multiple linear regression test and hypothesis testing using IBM SPSS 25 software. The results of this study indicate that if there is an increase in brand image and customer trust will also have an impact on increasing the level of customer loyalty. There is a partial influence of brand image on loyalty and between trust in loyalty, and there is a simultaneous relationship between brand image and trust in customer loyalty of Islamic banks in Sidoarjo.